PTK (PENELITIAN TINDAKAN KELAS) DENGAN PEMBELAJARAN BERBASIS KEARIFAN LOKAL DAN PENULISAN ARTIKEL ILMIAH DI SD NEGERI KALISUBE, BANYUMAS - Dini Siswani Mulia; Suwarno Suwarno (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
IbM activity aims to increase knowledge about local knowledge, improve skills develop proposals PTK Based Local Wisdom, compiling reports PTK (class action research) based Local Wisdom, and improve the skills of writing scientific articles. The method used in this activity is participatory learning and action (PLA), include: 1). coordination with partners in preparation for the implementation of the program, contact the team of experts, 2). preparation of several training modules to guide the activities, 3). training local wisdom Banyumas 4). technical training prepare proposals PTK Based Local Wisdom, 5). technical training prepare reports PTK Based Local Wisdom, 6). training technique of writing scientific articles, and 7). mentoring programs and evaluation. The result of this activity is the partner has insight into local wisdom Banyumas, and understand that PTK can be done using local wisdom as PTK Banyumas specific needs and character of students. Partners have the knowledge and skills in the preparation of proposals, the implementation of the PTK in the classroom, and the preparation of reports based on local wisdom PTK, partners have the knowledge and skill in preparing scientific articles, the partners have managed to draw up a report PTK and scientific articles have been published in scientific journals of education. Keywords: scientific articles, Banyumas, local knowledge, PTK (Classroom Action Research), SD Negeri Kalisube